Collaboration Network Model of HIV/AIDS Prevention and Control: Case Study in Subang District, Indonesia - Raharja, Sam'un Jaja; Akhmad, Dede (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
This study was conducted due to the increasing trend of people living with Human immunodeficiency virus infection and acquired immune deficiency syndrome (HIV/AIDS) (HIV/AIDS) in Subang Regency, West Java Province. This phenomenon was marked by high population mobility. Thus, this study aims to analyze the network model for HIV/AIDS prevention and control in Subang Regency. In this study, a networking approach by collaboration was adopted using six dimensions, namely, governance, administration, organizational autonomy, mutuality, norms and leadership. A qualitative approach is applied to explain a dataset which was a collection of observation and in - depth interview and supported by secondary data from relevant informants who are involved in preventing and reducing HIV/AIDS in Subang Regency. These informants were the actors who represent government agents and non-government organizations. Result showed that all dimensions of collaboration occur on an iterative, cyclical and dynamic process. However, on a practical approach, this model is implemented on a linear and causality basis and can explain a system towards problem-solving and new values forming.